Histamine test kit formation from Manganase (II), 5-fluorouracil and Alizarin red S complex compound - Hijriati Sholehah; Hismi Susane (Jurnal Pijar Mipa, 2020)
This researh aims to detect the presence of histamine by forming complex compounds of 5-fluorouracil, Mn (II) metal ions and alizarin red S reagents. This type of research is a laboratory experiment. This research was conducted at the Ikip Chemistry Laboratory in 2019. The results showed that the Test Kit that was made could be used to detect the presence of histamine determining the existence of histamine qualitatively viewable color formed based on complex compounds ofÃÂ  Mn(II)-His-5FU-ARS seen from the shift in wavelength of maximum generated.. The making of the histamine test kit is made by varying the concentration of 10-100 ppm at 10 ppmÃÂ ÃÂ  intervals under optimum conditions and can be used to make a color comparator solution. ThenÃÂ  the method validity test is done by making a standard histamine curve that gives a regression equationÃÂ  y = 0.001x + 0.3364 with a correlation coefficient (r2) = 0.9972. Based on the validity test method, the accuracy value is in the range ofÃÂ  95.0-106% and the results of the test kit on tuna samples indicate that the histamine test kit made has a good accuracy value because the average recovery value is 96%.ÃÂ